Islamic Investment and Capital Market: Analysis of Developments and Challenges in the Modern Era - Damayanti, Intan Amelia (Journal Corner of Education, Linguistics, and Literature, 2025)
The Islamic capital market has experienced significant growth in recent decades as an investment alternative compliant with Islamic principles. This development demonstrates that the Islamic financial system is not only an option for Muslims but is also beginning to attract the attention of global investors seeking more ethical and sustainable investment instruments. This article comprehensively analyzes the development of Islamic investment and capital markets, identifying their underlying principles and evaluating the challenges and opportunities faced in the context of the modern global economy. Using a descriptive-analytical approach, this study demonstrates that the Islamic capital market not only provides a halal investment alternative for Muslims but also offers stability and sustainability that can attract investors from diverse backgrounds. The unique characteristics of the Islamic capital market, which avoids riba (usury), gharar (gharar), and maysir (risk of gambling), create a strong foundation for more stable and sustainable long-term investment. These principles not only ensure compliance with Islamic teachings but also encourage more transparent and responsible business practices However, challenges such as global standardization, investor literacy, and product innovation still need to be addressed to maximize the potential of the Islamic capital market. Global standardization is crucial given that differences in sharia interpretations across countries can hinder cross-border market growth. Furthermore, the low level of investor literacy regarding sharia products requires ongoing educational efforts. Product innovation is also necessary to meet the increasingly diverse and dynamic needs of investors. By addressing these challenges, the Sharia capital market has significant potential to continue growing and make a significant contribution to the stability of the global financial system.